(untitled) (Khairulummah, 2023)
Dr Hakim: The modern era was blessed with the most prominent and iconoclast scholar Mirza Qaleech Baig in Sindhi literature.Sindi prose received great impetus by his countless efforts.He enriched Sindhi prose by writing original works of fiction and non fiction , adaption and translation.His services for Sindhi prose include numerous novels,dramas, history books, educational books, and dictionaries.He also contributed a lot in different genres of poetry.in this research paper an attempt has been made to analyze his services in Sindhi prose .